2019
DOI: 10.1039/c8ra09384a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of graphite/MgO-reinforced poly(vinyl chloride) composites by mechanical activation with enhanced thermal properties

Abstract: Fabrication of graphite/MgO reinforced poly(vinyl chloride) composites with enhanced thermal properties by mechanical activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Deconvolution of high-resolution O 1s spectra showed three oxygen-containing functional groups, namely, carbonyl oxygen atoms (CO, 532.7, 531.4, and 532.7 eV for graphite, N-doped graphite, and O-doped G, respectively), noncarbonyl oxygen atoms (C–OH, 534.8, 534.3, and 534.6 eV for graphite, N-doped graphite, and O-doped G, respectively) and oxygen atoms in carboxylic groups (COOH, 533.3 eV for O-doped G) (Figure S3d). Oxygenation and nitrogenation of the carbon scaffold in O-doped G and N-doped G caused an increase in the full width at half-maximum (FWHM) of their C 1s spectrum, indicating the presence of a greater amount of disorder in the carbon sp 2 network. It should be mentioned that the presence of O 1s distinct peak in the XPS spectra of graphite and N-doped G in Figure S3a is attributed to the adsorption of ambient water and oxygen by the samples and also slight oxidation of samples by oxygen when handled under the ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deconvolution of high-resolution O 1s spectra showed three oxygen-containing functional groups, namely, carbonyl oxygen atoms (CO, 532.7, 531.4, and 532.7 eV for graphite, N-doped graphite, and O-doped G, respectively), noncarbonyl oxygen atoms (C–OH, 534.8, 534.3, and 534.6 eV for graphite, N-doped graphite, and O-doped G, respectively) and oxygen atoms in carboxylic groups (COOH, 533.3 eV for O-doped G) (Figure S3d). Oxygenation and nitrogenation of the carbon scaffold in O-doped G and N-doped G caused an increase in the full width at half-maximum (FWHM) of their C 1s spectrum, indicating the presence of a greater amount of disorder in the carbon sp 2 network. It should be mentioned that the presence of O 1s distinct peak in the XPS spectra of graphite and N-doped G in Figure S3a is attributed to the adsorption of ambient water and oxygen by the samples and also slight oxidation of samples by oxygen when handled under the ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the values of R ct for O-doped GPE and N-doped GPE were about 654 and 897 Ω, respectively. The superior charge transfer rate at O-doped GPE and N-doped GPE compared to GPE and CGPE can be attributed to the increase of edge plane sites density or the increase of defect density and the surface chemistry of electrode materials. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies support these results. For instance, Qi et al [ 4 ] found that the melting temperature range of HDPE is 121.2–151.3 °C, and Li et al [ 29 ] confirmed that PVC exhibited an exothermic peak at 82.8 °C. The VPC could not support a high load when the thermoplastics were completely melted.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the PXRD patterns of various catalysts, which suggest the corresponding peaks for Al 2 O 3 and participating metals in their respective oxidic phase, that is, NiO (37°, 44°, and 63°), MnO 2 (18°, 22°, 31°, 40°, 54°, and 60°), Co 3 O 4 (32°, 34°, and 47°), and Mo (36°, 47°, and 58°). It is important to mention here that the vague and unclear nature of PRXD peaks in Figure could be concomitantly attributed to the highly powdered and ground nature of the catalysts and limitations of the XRD instrument (<5 wt % loadings of Mn, Co, and Ni). ,, However, a uniform morphological trend for all the catalysts was shown, which was due to a similar synthesis procedure, while the only difference arose in the variation of metallic species in different samples.…”
Section: Resultsmentioning
confidence: 99%